Mothering from the Inside Out: Adapting an evidence-based intervention for high-risk mothers in the Western Cape of South Africa. (February 2020) - Suchman, Nancy; Berg, Astrid; Abrahams, Lameze; Abrahams, Toni; Adams, Amy; Cowley, Brenda; Decoste, Cindy; Hawa, Waseem; Lachman, Anusha; Mpinda, Bulelwa; Cader-Mokoa, Nasera; Nama, Nosisana; et al.
Abstract: During South Africa's first two decades as a democracy, the Western Cape Province has undergone radical changes to its healthcare system in an effort to address the extensive socioeconomic inequities that remain in the aftermath of the apartheid era. Although progress has been made, there is a clear need for interventions that support parents and children receiving health services in the public sector who are vulnerable to multiple psychosocial risks associated with extreme poverty. In this mixed-method study, we examined the feasibility and acceptability of adapting an evidence-based parenting intervention called Mothering from the Inside Out that was developed for mothers who are vulnerable to similar risks in the United States. Using qualitative methods, we documented the collaborative process that was guided by principles of community-based participatory research and examined themes in the Western Cape collaborators' perspectives about the feasibility and acceptability of the intervention. Using quantitative methods, we tested the preliminary efficacy of the adapted version of Mothering from the Inside Out for improving maternal reflective functioning and mother–child interactions. Although findings from both study components indicated preliminary promise, a number of obstacles and challenges at multiple levels underscore the need for (a) flexibility and contextual support for intervention research conducted in under-resourced communities, (b) clinical sensitivity to the unique experiences of parents rearing children in highly stressful, under-resourced environments, and (c) equal partnerships that allow the expertise of local providers to inform the design proposals of consulting investigators.